2004
DOI: 10.1532/lh96.03030
|View full text |Cite
|
Sign up to set email alerts
|

Application of Receiver Operating Characteristics Curve (ROC) Analysis When Definitive and Suspect Morphologic Flags Appear in the New Coulter LH 750 Analyzer

Abstract: Workflow efficiency is important in every laboratory. Manual assessment of white blood cell counts and differentials that have been rejected by an automated analyzer is one of the most time-consuming tasks in the routine hematology laboratory. In this study, receiver operating characteristics (ROC) curve analysis was used for the first time when anomalous distribution and suspect flag alarms appeared in hemograms carried out with the new Beckman Coulter LH 750 analyzer. This article is our second about the LH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…FCM. The Area Under the Curve (AUC) was determined from the ROC analysis (Aulesa et al , 2004). The higher the AUC number the better the performance, with 0.50 indicating random performance and 1.00 denoting perfect performance.…”
Section: Methodsmentioning
confidence: 99%
“…FCM. The Area Under the Curve (AUC) was determined from the ROC analysis (Aulesa et al , 2004). The higher the AUC number the better the performance, with 0.50 indicating random performance and 1.00 denoting perfect performance.…”
Section: Methodsmentioning
confidence: 99%
“…Hoyer et al analyzed WBC flags generated by Coulter STKS studies have observed good correlation between WBC flags and leukemic blasts in PBF. [3][4][5][6][7][8] However, in a tropical nation where infectious diseases such as malaria and dengue pose a greater public health burden, the utility of the WBC flags in hinting toward an underlying infection is poorly understood and scarcely documented in the literature. [9][10][11][12] We undertook this study to analyze any abnormal flags generated by a three-part automated hematology analyzer in serologically confirmed cases of dengue and correlate with other hematological parameters and PBF findings in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,19,20 It is interesting, however, that slight variations also were observed in the results obtained depending on the reference method with which they were compared. Accordingly, the highest and the lowest coefficients of correlation for the 5 cell populations analyzed in normal and abnormal samples were obtained when the PENTRA 80 results were compared with flow cytometry and conventional microscopy, respectively; comparisons with the CELL-DYN 4000 showed intermediate correlation coefficients near those observed with flow cytometry.…”
Section: Discussionmentioning
confidence: 99%